Agaric acid reduces Salmonella biofilm formation by inhibiting flagellar motility - Bram Lories; Tom E.R. Belpaire; Anna Yssel; Herman Ramon; Hans P. Steenackers (Biofilm, 2020)
Salmonella biofilms are a common cause of contaminations in the food or feed industry. In a screening for novel compounds to combat biofilm-associated foodborne outbreaks, we identified agaric acid as a Salmonella Typhimurium biofilm inhibitor that does not affect planktonic growth. Importantly, the remaining biofilm cells after preventive treatment with agaric acid were significantly more sensitive to the common disinfectant hydrogen peroxide. Screening of a GFP-promoter fusion library of biofilm related genes revealed that agaric acid downregulates the transcription of genes responsible for flagellar motility. Concurrently, swimming motility was completely abrogated in the presence of agaric acid, indicating that biofilm inhibition occurs via interference with the motility phenotype. Moreover, agaric acid also reduced biofilm formation of Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli. Agaric acid thus shows potential as an anti-virulence compound that inhibits both motility and biofilm formation.